Does consciousness cause behavior? - Pockett, Susan; Banks, William P.; Gallagher, Shaun, 1948- (MIT Press, 2006)
Continuing the debate over whether consciousness causes behaviour or plays no functional role in it, leading scholars discuss the question in terms of neuroscience, philosophy, law and public policy.